Immediate effect of kinesiology tape on ankle stability - Slevin, Zack M (BMJ Open Sport Exerc Med, 2020)
BACKGROUND: Lateral ankle sprain is one of the most common musculoskeletal injuries, particularly among the sporting population. Due to such prevalence, many interventions have been tried to prevent initial, or further, ankle sprains. Current research shows that the use of traditional athletic tape can reduce the incidence of sprain recurrence, but this may be at a cost to athletic performance through restriction of motion. Kinesiology tape, which has become increasingly popular, is elastic in nature, and it is proposed by the manufacturers that it can correct ligament damage. Kinesiology tape, therefore, may be able to improve stability and reduce ankle sprain occurrence while overcoming the problems of traditional tape. AIM: To assess the effect of kinesiology tape on ankle stability. METHODS: 27 healthy individuals were recruited, and electromyography (EMG) measurements were recorded from the peroneus longus and tibialis anterior muscles. Recordings were taken from the muscles of the dominant leg during induced sudden ankle inversion perturbations using a custom-made tilting platform system. This was performed with and without using kinesiology tape and shoes, creating four different test conditions: barefoot(without tape), shoe(without tape), barefoot(with tape) and shoe(with tape). For each test condition, the peak muscle activity, average muscle activity and the muscle latency were calculated. RESULTS: No significant difference (p>0.05) was found by using the kinesiology tape on any of the measured variables while the wearing of shoes significantly increased all the variables. CONCLUSION: Kinesiology tape has no effect on ankle stability and is unable to nullify the detrimental effects that shoes appear to have.